THE ROLE OF ASYMMETRIC INFORMATION IN SHAPING INVESTMENT STRATEGIES: IMPLICATIONS FOR FINANCIAL MARKET STABILITY - يوسف أدينيي جاميو; أفولابي لقمان أولاجيد; أولودويي إسحاق أولاكونلي (مجلة الغري للعلوم الاقتصادية والادارية)
Asymmetric information, where one party has more or worse information than another, significantly impacts financial markets. This study examines how information asymmetry shapes investment strategies and its implications for financial market stability. We explore the theoretical underpinnings of asymmetric information using Principal-Agent Theory and the Efficient Market Hypothesis (EMH). The empirical analysis, using secondary data from 2000-2020, reveals a positive correlation between asymmetric information and market instability, while market liquidity has a negative correlation. The findings highlight the importance of mitigating information asymmetry to promote stable financial markets. Policy recommendations include stricter disclosure requirements, investment in transparency technologies, and investor education programs.